2012
DOI: 10.1111/j.1461-0248.2012.01767.x
|View full text |Cite
|
Sign up to set email alerts
|

A curve of thresholds governs plague epizootics in Central Asia

Abstract: Ecology Letters (2012) Abstract A core concept of infectious disease epidemiology is the abundance threshold, below which an infection is unable to invade or persist. There have been contrasting theoretical predictions regarding the nature of this threshold for vector‐borne diseases, but for infections with an invertebrate vector, it is common to assume a threshold defined by the ratio of vector and host abundances. Here, we show in contrast, both from field data and model simulations, that for plague (Yersini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 24 publications
1
47
0
1
Order By: Relevance
“…When the gerbil population is rapidly increasing in numbers, the flea population is diluted over a larger number of gerbils, decreasing the flea burden per gerbil. Vice versa, a decreasing gerbil population means that fleas will aggregate on the remaining hosts, thus causing a high flea index, and facilitating the rapid transmission of plague [45].…”
Section: Discussionmentioning
confidence: 99%
“…When the gerbil population is rapidly increasing in numbers, the flea population is diluted over a larger number of gerbils, decreasing the flea burden per gerbil. Vice versa, a decreasing gerbil population means that fleas will aggregate on the remaining hosts, thus causing a high flea index, and facilitating the rapid transmission of plague [45].…”
Section: Discussionmentioning
confidence: 99%
“…Plague prevalence among great gerbils (Rhombomys opimus) in Kazakhstan is strongly positively affected by warmer springs and wetter summers (9), and correlates with the population density of the gerbils and fleas themselves (10). When climatic conditions uniformly affect large geographic areas, they can synchronize gerbil densities at the regional scale (11) in a process known as the Moran effect (12,13).…”
mentioning
confidence: 99%
“…Currently, no empirical data exist to define a burrow density threshold value. However, models such as the flea-density-threshold model [15] predict occupied burrow density threshold values below which no invasion of plague can occur. However, as the occupancy varies over space and time these modelled values cannot be translated into a single threshold burrow density value.…”
Section: Discussionmentioning
confidence: 99%
“…In Eastern Kazakhstan, the presence of this pathogen has been monitored in great gerbils ( Rhombomys opimus ), social rodents that live in burrows, for decades. It has been found that outbreaks of plague occur only when a host and flea abundance threshold is exceeded [14,15], but the direct influence of the landscape on spatial spread and the dynamics of this disease has not previously been investigated.…”
Section: Introductionmentioning
confidence: 99%